Pile Analysis With Dynamic and Static Tests of Manufacturing Permit Capacity - Dian Kurniawan Tanjung (Eduvest - Journal of Universal Studies, 2025)
This article discusses the analysis of pile bearing capacity using dynamic and static tests to evaluate the capacity of manufacturing permits in the construction project of the X Shoe Factory in Pekalongan, Central Java. The study aims to determine the ultimate bearing capacity of piles by applying various formulas, such as Meyerhoff, Poulos & Davis, Schmertmann, Coyle & Castillo, and the Alpha & Lambda Method, which take into account corrected NSPT values and CPT data. Additionally, the study validates the calculation results through static and dynamic testing, and compares these results with the allowable loads specified in the design and manufacturing management standards. The analysis revealed that the 1956 Meyerhoff method, when combined with the Terzaghi correction for NSPT data, produced results closest to the empirical test values, while the modified ENR formula yielded reliable outcomes for dynamic analysis. This research is expected to enhance efficiency in the selection of appropriate pile foundation systems for future manufacturing facility construction projects.